Mathematical Modeling and Optimization of Platform Service Supply Chains: A Literature Review - Xiaotong Guo; Yong He (Mathematics, 2022)
With the increasing importance of the platform service supply chain (PSSC) in creating economic value, academic research is paying more and more attention to it. The current literature’s research topics and problems cover broad areas. This review adopts bibliometric analysis and thematic analysis to review the related literature systematically and comprehensively. We divided the literature about PSSC into six groups according to the literature’s research topic and research question. Each literature’s research problem and research method are categorized and summarized. Our review results demonstrate that the supply chain’s members’ operational decisions and the supply chain’s coordination are two main types of research questions. Pricing decisions have received the most attention. In terms of the research method, game models are the most common method used in research to achieve the optimization of the PSSC.